Relatório de Estágio Profissional "Disciplina e Organização: Fatores Essenciais para o Sucesso" - Alexandra Rangel Marques (2017)
The practicum presents itself as the first chance where it is possible to apply all the theoretical knowledge acquired throughout the years, in a practical, but yet controlled environment. The symbiotic relationship between theory and practice enhances the constant evolution of the preservice teacher. Within practicum it is expected that the preservice teacher live the full experience of what means to be a teacher, since this process has several resemblances with the future professional activity, causing an important personal and professional evolution. By the end of this process, the preservice teacher presents the re-sults of its work in this practicum report. This document aims to present and discuss all the activities proposed and realized, and the actuation of the preservice teacher throughout its practi-cum. Being so, this document contemplates five main chapters. The first chap-ter, introduction, explains the motivation for the development of this practicum report. Then, in the following chapter, a biographical context of the preservice teacher is presented. In the third chapter, this is divided in four different sec-tions: a brief presentation of the practicum program, the institutional and legal framework of the practicum process, school as an institution, and the key per-sons in this process. The fourth chapter is divided in three areas: organization and management in the teaching-learning process, involvement within the school community and the professional development which is a research study that discusses the influence of a thirteen weeks strength training program in twelfth grade students. Finally, the conclusions and the future work perspectives are discussed in the last and fifth chapter.